RANCANG BANGUN AUTOMATIC CAT LITTER BOX BERBASIS ARDUINO UNO - Rendi Ronaldi; Sumpena Sumpena (JURNAL TEKNOLOGI INDUSTRI, 2019)
A litterbox is an indoor litter and urine collection box for cats or rabbits, ferrets, small dogs and other pets that use such a repository. The existing Litterbox has a weakness in keeping the Litterbox in a clean condition and its maintenance is complicated. So we need a tool to facilitate human activities or to support the busyness of various activities, especially cat caretakers.For that purpose, an